Performance and carcass traits of Nellore cattle fattening on pasture receiving different zinc contents in the mineral supplementation - Julliano Percinoto Pompei; Geisi Loures Guerra; Elzânia Sales Pereira; Leandro das Dores Ferreira da Silva; Patrícia Guimarães Pimentel; Edson Luis de Azambuja Ribeiro; Taís Aline Bregion dos Santos; Angelita Xavier dos Santos; Mariellen Cristine Andrade Ribeiro; Ivone Yurika Mizubuti (Semina: Ciências Agrárias, 2018)
The objective of this work was to study the effect of different zinc content (ZnSO4) in the mineral supplementation for Nellore steers grazing Brachiaria brizantha (cv) MG-4, on productive performance and carcass traits. Twenty-eight castrated animals with average body weight of 355 kg, were used. The animals were randomly divided into four groups and housed in paddocks of 6.25 ha each one, equipped with covered feeders and waterers, and grazed alternately each 28 days. The experimental design was completely randomized, with four zinc (Zn) content and seven repetitions. Different zinc content were: Zn-0, without Zn; Zn-2, with 2,000 mg Zn kg-1; Zn-4, with 4,000 mg Zn kg-1; and Zn-6, with 6,000 mg Zn kg-1; in the inorganic form (Zinc Sulphate) in mineral supplement. Mineral supplements were given ad libitum in covered troughs and previously weighed, with leftovers control for determining intake. The experimental period was 370 days. Organs, viscera, carcass and non-carcass components were weighed from each slaughtered animal. Loin eye area (LEA) and subcutaneous fat thickness (SFAT), as well as, color, pH and lipid oxidation, were evaluated. The increasing inclusion of zinc content in the diet of steers do not affected (P > 0.05) final body weight (FBW) and average daily weight gain (ADWG). Difference (P < 0.05) was observed in the Zn intake (ZnI) (? = -2.09386 + 146.9616x; R2 = 0.99) and hot carcass weight (?= 299.92662 + 3.33362x; R2= 0.24), as well as, in meat lipid oxidation (? = 0.15170 + 0.02539x; R2= 0.31). There was an increasing linear effect for meat color, evaluated by values of L* (luminosity) (? = 32.23309 + 0.41445x, R2 = 0.14), a* (red-green intensity) (? = 0.88592 + 18.16225x, R2 = 0.25) and b* (yellow-blue intensity) (? = 9.35295 + 0.45030x, R2 = 0.20), but remained within normal values for meat. It can be concluded that beef cattle grazing Brachiaria brizantha MG-4, and supplemented with different zinc contents in mineral supplements, supplied ad libitum, do not show changes in weight gain, carcass yield, physical carcass composition, as well as, in non-carcass components, but the Zn content has a positive linear influence on hot carcass weight, without causing changes in absolute and relative weights of organs and viscera.